Hubungan Sikap Caring Perawat Dengan Tingkat Kepuasan Pasien Rawat Inap Rumah Sakit Santo Antonio Baturaja - Supriati, Theresia; Hastuti, Ag.Sri Oktri; Noviati, Bernadetta Eka (STIKes Panti Rapih, 2024)
Background Health services are designed to enable humans to live. In addition to having good facilities and infrastructure, the professionalism of health workers is also important for its success. A nurse is now one of the professions that can save lives because of its holistic role in fulfilling human life. One indicator of the quality of nursing services is patient satisfaction and nurse attention, which is evidence of the quality of nurse services. Patient satisfaction is very dependent on how well nurses treat patients. The purpose of this study was to determine the relationship between nurse caring attitudes and patient satisfaction levels at Santo Antonio Baturaja Hospital. This study method uses a descriptive correlational research design and cross-sectional data collection techniques. The sample for this study was 101 respondents using the random sampling method to collect data using a questionnaire on nurses' caring attitudes and patient satisfaction. 62.37%) and argued that nurses have caring behavior (57.42%) with a p-value of 0.000 ˂ 0.05. The conclusion from this study is that there is a relationship between nurse-caring attitudes and patient satisfaction at Santo Antonio Baturaja Hospital. Suggestions from this study are that nurses are expected to maintain the quality of nursing care so that patient satisfaction can be maintained.